DIREITO DO NATIMORTO AO PRÓPRIO NOME - SANTANA, JONATHAS (2022)
The research has as its general purpose to proceed the analysis regarding the name suitability in the stillborn certificate and the theoretical as well as legislative jurisprudential scope of exercising the right to a name; the specific objectives are: to verify the theoretical lines elaborated about the right to a name, the personality and the figure of the stillborn child; to relate theories of the beginning of a legal personality with the name; and to appreciate the relationship between the right to mourning and personality as foundation for safeguarding the stillborn child's right to their own name. The theme addresses the matter of the suitability and ownership of the stillborn's right to a name; the problem lies in the perception of the contradictory way in which the legal system, mainly the general internal affairs departments of the justice courts of the States, treats the stillborn child's right to their own name and the previously elaborated hypothesis is that the name fits in the death certificate of the stillborn child , as a right of personality to which it is entitled. The theme relevance indicates the lack of definition that hovers over the elements to appear in the death certificate of the stillborn child, including the name, in accordance with article 53, paragraph 1 of the 1973 Public Records Act, whose study helps to understand the legal treatment that would be due to stillbirth. The research is monographic and follows the legal-dogmatic method of approach and the legal-purposeful procedure; in addition, the data collection technique used is the bibliographical one. The structure of the chapters portrays the investigation made about the three existing perspectives regarding the name, personality and stillbirth, in the first chapter; the comparison of theories of the beginning of a personality, made from the perspective of the right to a name of the stillborn child before the Brazilian legal system, in the second chapter; and, in the third chapter, the examination of the problem of the stillborn child's right to their own name, based on the right to mourning and personality rights besides their coexistence in the national legal system. The main result targets to the fact that, among the perspectives for meeting the demands of the stillborn, the one whose reason is its own figure is best suited, considering the theoretical propositions formulated in connection to the fruition of the right to a name, the stillborn and the personality; the conceptionist theory, among those that were investigated for dealing with the problem of the beginning of a legal personality, is the one that best explains the faculty and/or obligation of inserting the name in the stillbirth declaration. Moreover, in what concerns the motto of the relationship between the foundation of personality and the right to mourning as skillful tools to provide the exercise of the right to a name by the stillborn, the conclusion refers to the obligation of inserting the name in the death certificate - under its ownership -, including in order to alleviate the pain of mourning, making it necessary to amend article 53 of the Public Records Law of 1973 to oblige the inclusion of the name in the death certificate of the stillborn child, including with a focus on the wording of the Article 584 of the Code of Extrajudicial Norms of the State of Bahia.